Sprint vs intermittent training in young basketball players - Padulo, J.; Attene, G.; Bramani, S.; Pizzolato, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In young basketball players, it is not known whether sprint or intermittent training fulfils the criterion of effective training to improve sprint vs endurance. The aim of this study was to compare the effects of intermittent training and repeated sprint ability training (Ferrari Bravo et al.; 2008) on physiological variables in female basketball players. Methods: Sixteen participants were randomly assigned to either the intermittent training group (YYIRG, n= 8) or repeated-sprint training group (RSAG, n= 8). The following outcomes were measured at baseline and after 6 weeks of training: Yo-Yo IRT (YYRT) and RSA tests (Castagna et al.; A-B 2008). The YYIRG performed at the 80% of the maximal speed (YYIRT) 3 sets of 5` of shuttle running (16.47±0.61m - total time 20"), with 20" of recovery and 3` between sets. The RSAG performed (15+15m) with repeated sprint training:3 sets of six maximal sprint with 20" of recovery and 4` between sets. Result: The main effect of training type for all the variables investigated was never significant. In the RSA, best time (BT) was found a significant main effect of time (pre vs post) (p< 0.0001), and the interaction training type x time (p< 0.03). The RSAG showed a decrease in the BT by 3.1% (p< 0.005) and the YYIRG showed a decrease by 6.2% (p< 0.0001). Significant main effect of time in the worst time, with a decrement of 5.36%; in the total time, with a decrement of 5.08%; in blood lactate with a decrement of 24.02%. In the YYIRT significant main effect of time in the distance with an increment of 26.9%. Significant main effect of time in the final speed with an increment of 1.23%. Discussion: These findings suggest that the two training protocols used in this study can be an effective training strategy for inducing anaerobic and basket-specific training adaptations. Therefore, even weather the YYIRG training is not done at very high speed, it can more increase the maximum speed of the RSAG. Moreover, given that the two trainings are different in terms of volume of work, we can suggest choosing the RSA training in team sports when we want to reduce the volume of work without compromising the anaerobic fitness.